Switzerland : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses key findings of the Financial System Stability Assessment on Switzerland. Stress tests indicate that the Swiss banks are robust against even severe shocks. Banks have increased their capital, and the two global banks have achieved substantial deleveraging. Swiss Financial Market Supervisory Authority has focused on significantly improving the quality of its supervision. Real estate bubbles appear to be emerging. With monetary instruments not available, macroprudential instruments are being introduced, but so far are limited and untested. Interest rates are negative at some maturities, threatening the business models of life insurance and pension companies.